The Effect of Liquid Organic Fertilizers in The Refugia Block on Visiting Insects in The Apple Orchard and Community Knowledges in its Conservation Efforts - Mohamad Nasirudin; Amin Setyo Leksono; Nia Kurniawan (Jurnal Pembangunan dan Alam Lestari)
This study aims to determine community structure and composition of liquid organic fertilizer (POC) against visiting insects in block Refuge and to determine the public perception of the block Refuge and insect’s conservation. Analysis of insects data are obtained from the important of index value, diversity (index’s Shannon Wienner). Insect abundance spring that treatment total 298 individuals and control 168 individuals. Insect abundance spring that treatment total 262 individuals and control 116 individuals. Insect diversity during flowering season given treatment was 2,11 andcontrol 1,49. Diversity during fruiting season was similar, given treatment it was 1,87 and control 1,42. Abundance of insect on both seasons with treatments and control had a significance of P=0,004. Similarities between insects on flowering season treatments between fruiting season treatments between organic fertilizers of different seasons 0,94 and control 0,80. Analysis on abiotic factors correlated with insect abundance with R-square value of 15%. Local perception towards refugia blocks was found to be low (46%) and medium (48%). Local perception towards convservation was found to be low (34%) and medium (63%). Local perception is affected by knowledge and non responsive actions towards insect conservation.